Pengaruh Penerapan Pendekatan Saintifik terhadap Kemampuan Berpikir Kreatif Siswa SMA pada Materi Minyak Bumi - Andriani, Reni Andriani; Zulkarnain Gazali (Jurnal Bintang Pendidikan Indonesia, 2024)
This study aims to determine the effect of applying a scientific approach on students' creative thinking abilities. This research is an experimental study. The research design used was Pretest Posttest Only Control Group Design with a population of all grade X students totaling 64 students spread across 3 classes. Sampling is done by cluster random sampling. Class XB is taught using a scientific approach while class XA uses conventional methods. The research data is the ability to be analyzed using the sample t test indenpendent test with the help of Ms.excel 2017. Based on the results of statistical tests of students' creative thinking skills, a calculated t value = 1.94 > t table = 1.687 so that it can be concluded that the scientific approach affects students' creative thinking ability on petroleum materials.